Model Aplikasi Pengolahan Data Nilai Siswa Pada Sekolah Dasar - Nidia Rosmawanti; Muslihuddin Muslihuddin; Irma Irma (STMIK Banjarbaru, 2022)
Processing of data on the assessment of elementary school student learning activities is still done manually, resulting in late publishing of students' final grades in report cards and in the school information system. This study aims to develop applications that can be used to process assessment data on student learning activities. System development uses a prototyping model, involving system users in all aspects of design from the initial stage to the final stage. This system design uses UML (Unified Modeling Language) design tools, PH programming language and MySQL database, as well as testing based on the Blackbox Testing method. Application Model Data processing for the assessment of student learning activities developed can help speed up the process of presenting the final grade by the homeroom teacher, so that students and the student's family environment can quickly obtain information on the final grades of learning.Keywords: Software, Web-Based, Unified Modeling Language, Blackbox Testing. Abstrak. Pengolahan data penilaian aktivitas belajar siswa Sekolah Dasar yang masih dilakukan secara manual, mengakibatkan penerbitan nilai akhir siswa pada buku raport maupun pada sistem informasi sekolah menjadi terlambat. Penelitian ini bertujuan Untuk mengembangkan aplikasi yang dapat digunakan untuk mengolah data penilaian aktivitas belajar siswa. Pengembangan sistem menggunakan model prototyping, dengan melibatkan pengguna sistem dalam segala aspek perancangan mulai dari tahap awal hingga tahap akhir. Desain sistem ini menggunakan tools desain UML (Unified Modelling Language), bahasa pemrograman PH dan basis data MySQL, serta pengujian berbasis metode Blackbox Testing. Model Aplikasi Pengolahan data penilaian aktivitas belajar siswa yang dikembangkan dapat membantu mempercepat proses penyajian nilai akhir oleh wali kelas, sehingga siswa dan lingkungan keluarga siswa dapat memperoleh informasi nilai hasil akhir belajar dengan cepat.Kata kunci: Perangkat Lunak, Berbasis Web, Unified Modelling Language, Blackbox Testing.